2023
DOI: 10.3390/microorganisms11092341
|View full text |Cite
|
Sign up to set email alerts
|

Myco-Synthesized Selenium Nanoparticles as Wound Healing and Antibacterial Agent: An In Vitro and In Vivo Investigation

Heba El-Sayed,
Mostafa Y. Morad,
Hana Sonbol
et al.

Abstract: Bacterial-associated wound infections are an obstacle for individuals and the medical industry. Developing versatile, antibiotic-free therapies helps heal wounds more quickly and efficiently. In the current study, fungal metabolites were employed as a reducing agent in fabricating selenium nanoparticles (SeNPs) for improved antibacterial and wound healing properties. Utilizing UV-visible spectroscopy, dynamic light scattering (DLS), zeta potential, X-ray diffraction (XRD), and electron microscopic examination,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Therapeutic Capabilities : In addition to their diagnostic functions, theranostic agents have therapeutic components designed to deliver targeted treatment. This could involve drugs, nanoparticles, or other therapeutic agents that are tailored to act on specific cells or tissues [ 356 , 357 ].…”
Section: Nanotheranostic Agentsmentioning
confidence: 99%
“…Therapeutic Capabilities : In addition to their diagnostic functions, theranostic agents have therapeutic components designed to deliver targeted treatment. This could involve drugs, nanoparticles, or other therapeutic agents that are tailored to act on specific cells or tissues [ 356 , 357 ].…”
Section: Nanotheranostic Agentsmentioning
confidence: 99%
“…By adding ~30 nM sodium selenite to mesenchymal stem cells, Heo demonstrated increased proliferation of these cells and enhanced anti-inflammatory and angiogenic properties of exosomes in vitro and in vivo, which improved dermal fibroblast migration and wound healing [24]. Recently, other groups have demonstrated that topical application with inorganic selenium improved wound healing and collagen deposition in animal models [25][26][27][28][29][30]. However, it is still unclear if the selenium carrier, inorganic versus organic, is relevant to ECM production and its redox impact on living human fibroblasts.…”
Section: Introductionmentioning
confidence: 99%